PENERAPAN PENDIDIKAN KONSELING ISLAM DALAM MEMBINA PERILAKU SOSIAL ANAK JALANAN DI HARJAMUKTI KOTA CIREBON - admin, admin; Sofy, Malik (THORIQOTUNA: Jurnal Pendidikan Islam, 2021)
This study aims to obtain data on the causes of social behavior of street children and to investigate data about the application or the form of social services of religious guidance in fostering social behavior in Harjamukti Cirebon City. This research is a field research and the method that I use is a qualitative method. Based on the discussion in this study, it can be concluded that the factor is the cause of street children, the family, the community, and of the structure of society (economic, social, cultural and political). Application of Islamic counseling conducted social services and society in general, and specifically in the prevention of street children was set up shelters and PNPM (national community empowerment program) in which will give more education and skills to street children.